(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2019)
To ascertain the sanctuary status on diversity and production of fishes data were collected through primary and secondary sources. A total of 64 species belonged to 48 genera including fish (57), freshwater prawns (2), crabs (1) and mollusks (4) were recorded. Of 57 fish species, 52 were indigenous and rest 5 exotic, which belonged to 9 orders and 24 families. Cypriniformes was the most dominant order with 33.33% of total fishes followed by Perciformes (24.56%), Siluriformes (22.81%), Channiformes (7.03%) and both Osteoglossiformes and Clupeiformes (3.51%). Rest orders showed comparatively less percentage. Cyprinidae occupied the highest position (29.82%) in fish population among recorded families. By percent contribution small indigenous species showed the highest contribution (38.86%) with the highest amount (1936.50 kg/ha) in total fish production than other groups. Average fish production in sanctuaries obtained as 4983.60 kg/ha, which is manifolds higher than haor fish production (408 kg/ha) in Bangladesh. Fifteen (15) fish species were found as threatened and categorized them into critically endangered (1), endangered (8) and vulnerable (6). Results of the study reveal that sanctuary has positive impact on diversity and production of fishes in the haor. Therefore, it may be concluded that restoration of threatened species, diversity of flora and fauna, and overall fish production may be increased in wetlands by establishing sanctuary. Asiat. Soc. Bangladesh, Sci. 45(2): 175-186, December 2019